Aprovechamiento de la cáscara de naranja (Citrus X sinensis) para la obtención de extracto esencial como un desengrasante natural - Balarezo Saltos, Luis David (2021)
The objective of this investigation was to use the residues of orange to obtain an essential extract, formulating a natural degreaser. A diagnosis was made through an interview with the company “Juices Sunset”, located in Guayaquil, province of Guayas, resulting that, of the total amount of the different processed fruits, half are residues without any kind of exploitation. The collection of the essential extract was developed under the technique of direct extraction at reflux and for the determination of the quality of the extract, the following parameters were measured: pH, total solids, % acidity, relative density and determination of limonene. Glycerin and betaine were used as study factors, as well as being environmentally friendly substances. For the formulation of the natural degreaser, a bifactorial DCA was applied with THE ADEVA and Tukey test at 95% significance. As a result, significant difference only in pH variable. In the application of the natural degreaser, pH and turbidity were measured, in which the interaction of 150 ml of orange extract and 15% of betaine (A2B1) obtained a greater detachment of lubricating grease. Compared to other interactions with a value of 2471 NTU and a pH of 5,46. Finally, the cost of producing 1 L of natural degreaser with a value of $5,67 was determined.